Optimizing Alternative Wind Power For Energy Efficient Building Design In Tropical Bot-Humid Climate Of Malaysia - Khalid, Hirda Lailani (2021)
Located near the Equator, Malaysia has a great advantage of solar energy as it abundantly available and people making use of it using solar photovoltaic to generate electricity. Malaysian wind however is light, variable and calm making it unreliable as an alternative energy and too low to naturally ventilate indoor spaces. As the result, most Malaysians resorted to use air-conditioning systems to achieve thermal comfort thus avoiding polluted air. The modem fully air-conditioned buildings are creating urban heat islands hence contributing to global warming.